EFFECT OF SOCIAL MEDIA ON MALAYSIAN EDUCATION: A MIXED-METHOD STUDY - Khan, Ambareen; Barkhaya , Nurul Maziah Mohd; Sanguman , Mageswaran; Akhtar , Mohammad Nishat (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
This study investigates the impact of social media on Education among Malaysian students through a mixed-method survey of 48 respondents. The research aimed to identify the positive and negative effects of social media, assess its overall impact on learning, and explore the challenges it presents in academic settings. The results reveal that social media enhances communication, critical thinking, engagement, and access to educational resources. The integration of artificial intelligence (AI) was also found to reduce human error and personalize learning experiences. However, issues such as distraction, addiction, and mental health challenges were also identified. The findings suggest that while social media provides powerful tools for modern education, practical guidance and digital literacy training are crucial to mitigate its negative impacts. The study concludes that with appropriate management, social media can be a transformative tool for enhancing educational quality and student performance in Malaysia.